Exploring Eu3+-doped ZnO-SiO2 glass derived by recycling renewable source of waste rice husk for white-LEDs application - Mohamed Khaidir, Rahayu Emilia; Fen, Yap Wing; Mohd Zaid, Mohd Hafiz; Matori, Khamirul Amin; Sheh Omar, Nur Alia; Anuar, Muhammad Fahmi; Abdul Wahab, Siti Aisyah; Khirel Azman, Aisyah Zakiah (Elsevier, 2019)
In this work, zinc silicate glass system (ZnO-SiO2) doped with various europium ion (Eu3+) concentrations derived from white rice husk ash (WRHA) were synthesized using melt and quench method. All samples determined by X-ray diffractometer (XRD) showed amorphous phase structure. The surface micrographs detected by Field emission scanning electron microscopy (FESEM) showed Eu3+ addition had reduced the sample’s porosity. Fourier transform infrared (FTIR) revealed the presence of Eu3+ ions had weakened the absorption peaks of SiO4. Meanwhile, ultra-violet visible spectroscopy (UV–vis) showed the absorption edges were shifted towards higher wavelength with Eu3+ addition. Band gap values were increased from 2.97 eV to 4.23 eV when Eu3+ dopant increased but decreased back to 3.98 eV at highest concentration. Photoluminescence spectroscopy (PL) analysis showed intense red emission at 600 nm corresponding to 5D0 → 7F2 transition were enhanced by Eu3+ doping. Hence, their luminescent properties are useful for optical device such as white light emitting diodes.